Mind the Map: How Thinking Maps Affect Student Achievement - Dan Jacob Long; David Carlson (Networks: An Online Journal for Teacher Research, 2011)
This action research project, conducted in an 8th grade classroom by Daniel Long, investigated how Thinking Maps could be utilized by the students to broaden critical thinking skills and enhance their understanding of the content being presented. The research data was gathered through anonymous student surveys, instructor observation notes and a post-intervention assessment. Students were taught the function and proper construction of all eight Thinking Maps and were encouraged to utilize them on multiple occasions every day. The findings by Long indicated that when students constructed Thinking Maps, they were able to achieve greater understanding than those students who used traditional note taking strategies. The purpose of this research was to determine if the use of Thinking Maps would increase student achievement. Because Thinking Maps allow students to express their thoughts and ideas non-linguistically, instructors actually see the graphic representation of a student’s thought process (Holzman, 2004). Thinking Maps differ from graphic organizers because they are used to promote “more strategic thinking” and encourage students to focus on the processes used to produce the “correct” answer (Holzman, 2004). By coaching students to correctly use the Thinking Maps in their daily lessons, students will have a greater sense of control of the way they handle classroom material and provide a strategy for organization that will allow them to form meaningful connections with the content.